Social Entrepreneurship and Agricultural Transformation in Malaysia - Intan Nursyahila binti Mohamad Basri; Mia Aulina Lubis (Talenta Publisher, 2024)
Social entrepreneurship in agriculture has emerged as a critical strategy to address Malaysia's challenges of food security, sustainability, and rural development. This study explores how social enterprises, such as Poptani Asian, are leveraging technology to promote sustainable farming practices, enhance agricultural productivity, and improve the livelihoods of rural communities. By empowering farmers with innovative tools and resources, these enterprises are contributing to local food production and reducing reliance on imports. The research highlights the significant role of social entrepreneurship in driving Malaysia's agricultural transformation and the challenges faced in achieving widespread impact. The study also discusses the potential for collaboration between the government, private sector, and consumers to overcome barriers and create a sustainable and resilient agricultural ecosystem in Malaysia.